Dynamic RNA Coding Color Image Cipher Based on Chain Feedback Structure - Wen, Heping; Kang, Shenghao; Wu, Zhuxi; Lin, Yiting; Huang, Yiming (Mathematics (Basel), 2023)
This paper proposes a dynamic RNA-encoded color image encryption scheme based on a chain feedback structure. Firstly, the color pure image is decomposed into red, green, and blue components, and then a chaotic sequence based on plaintext association is introduced to encrypt the red component. Secondly, the intermediate ciphertext is obtained by diffusion after encryption by bit-level permutation, RNA dynamic encoding, RNA dynamic operation rules, and RNA dynamic decoding. Finally, to enhance the security of the image cryptosystem, the green and blue components of the image are repeatedly encrypted using the chain encryption mechanism associated with the intermediate ciphertext to obtain the color cryptographic image. In this paper, a 2D-SFHM chaotic system is used to provide pseudo-random chaotic sequences, and its initial key is calculated by combining the hash function and external parameters of the image, and the one-time ciphertext encryption strategy causes the proposed encryption to effectively resist cryptographic attacks. Experimental results and security analysis show that our encryption algorithm has excellent encryption effects and security performance against various typical attacks.